REGARDING THE PROBLEM OF THE CONSEQUE NCES OF COVID INFECTION. CLINICAL CASE - Ніколаєнко-Камишова, Тетяна; Чумак, Володимир (SWorldJournal, 2024)
Manifestations of immuno-inflammatory syndrome in the form of autoimmune reactions against the background of comorbid pathology lead to the development of complex, and sometimes severe, clinical situations. On the example of the considered clinical ca